The International Sexual Health And REproductive Health during COVID-19 (I-SHARE) Study: A Multicountry Analysis of Adults from 30 Countries Prior to and During the Initial Coronavirus Disease 2019 Wave - Erausquin, Jennifer Toller (OXFORD UNIV PRESS INC, 2024)
10.1093/cid/ciac102